The adoption of metaverse in the retail industry and its impact on sustainable competitive advantage: moderating impact of sustainability commitment - Yogesh Dwivedi (Annals of Operations Research, 2024)
The concept of the metaverse involves creating a fully immersive virtual world that allows users to interact with each other and digital objects in a way that is almost indistinguishable from reality. One of the key areas where the metaverse is expected to have an impact is retailing. Although there have been several studies on the use of the metaverse in different industries, this issue is rarely investigated in previous studies in the context of retail companies focusing on users’ perceptions. This study accordingly explores the factors impacting the adoption of a metaverse in the retail industry and develops a new model based on the Resource-Based View (RBV) theory. In addition, the relationship between the usage intention of the metaverse and product innovation, and the relationship between product innovation and sustainable competitive advantage are investigated. Furthermore, as sustainability is a critical issue in the adoption of innovation by industries, this study aims to further investigate whether sustainability commitment will strengthen the impact of attitude toward metaverse on the intention to use. The data was collected from retail companies in Malaysia and analyzed to evaluate the proposed research model. The outcomes of this research indicated that there is a positive impact of product innovation on sustainable competitive advantage through the adoption of a metaverse in retail companies. In addition, our findings stressed that the intention to use metaverse will lead to product innovation in retail companies. Furthermore, the results revealed that sustainability commitment does not moderate the relationship between attitude toward the metaverse and intention to use, but impacts the usage intention of the metaverse directly.